Contractile rate of force development after anterior cruciate ligament reconstruction - a comprehensive review and meta-analysis - Turpeinen, J. T.; Freitas, T. T.; Rubio-Arias, J. A.; Jordan, M. J.; Aagaard, P. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Background: The recovery in rapid force production measured as the rate of force development (RFD) is not clear after anterior cruciate ligament reconstruction (ACLR). Objectives: To evaluate (a) time-course change of between-limb asymmetries in isometric knee extension/flexion RFD in individuals post-ACLR and (b) differences in RFD between individuals post-ACLR and healthy controls. Methods: A literature search of Web of Science, SPORTDiscus, PubMed-MEDLINE, and ScienceDirect identified 10 eligible studies (n = 246) assessing RFD after ACLR. Results: Standard mean difference (SMD) for early-phase (<100 ms) knee extensor RFD was -1.07 (95% CI: -1.46, -0.68) when comparing ACLR vs uninjured limb, while SMD for late-phase (=100 ms) RFD was -0.85 (95 CI%: -1.27, -0.42). SMD for early- and late-phase knee flexor RFD was -0.74 (95% CI: -1.19, -0.29) and -0.79 (95% CI: -1.19, -0.39), respectively. Comparing ACLR limbs to uninjured controls, knee extensor SMD for early- and late-phase RFD was -1.42 (95% CI: -2.10, -0.73) and 1.09 (95% CI: -1.81, -0.38). For the knee flexors, SMD for early- and late-phase RFD was -0.78 (95% CI: -1.96, -0.39) and -1.14 (95% CI: -1.60, -0.67). Conclusions: Anterior cruciate ligament reconstruction limbs demonstrated sustained post-surgical suppression in RFD capacity for the knee extensors/flexors compared to the contralateral limb as well as to healthy controls. Monitoring of RFD should be considered throughout rehabilitation and return to sport (RTS) after ACLR to assess the effectiveness of post-operative rehabilitation. Post-surgical ACLR rehabilitation should include training interventions to enhance RFD.